Możliwości współczesnej recepcji utworów Stanisława Jachowicza, dydaktycznej literatury dziewiętnastowiecznej - Beata Telatyńska (Problemy Wczesnej Edukacji)
Prior to the nineteenth century, literature aimed particularly at children did not exist. Only romanticism saw the great potential that the engagement with the topic of childhood offered. In Poland Stanislaw Jachowicz – Polish storyteller, educator and charity activist-achieved s significant successes in this field. In this article, the author presents Jachowicz’s work from two perspectives. By conducting a nineteenth century and a contemporary reading of his narrations, she examines the possible contexts of reading Jachowicz’s didactic literature, concentrating primarily on his fairy tales. Although, from the point of view of contemporary pedagogy, Jachowicz’s educational methods are outdated and inadequate to give guidance on the realities that the children of today face, one can find universal elements in the writer’s work, for example, respect for another person, work, money or empathy. The modern reader is invited to gain a better understanding of the realities of the nineteenth century family and confront these insights with the challenges and the hopes of the present day.